Superalloys 718, 625, 706 and Various Derivatives (2001) 2001
DOI: 10.7449/2001/superalloys_2001_173_183
|View full text |Cite
|
Sign up to set email alerts
|

718 Superalloy Forging Simulation: A Way to Improve Process and Material Potentialities

Abstract: In a forged condition, 71 8 superalloy is commonly used to manufacture some aircraft engine turbine parts severely loaded in service. The mechanical behavior of these parts depends on both thenno-mechanical conditions during flights and microstructural characteristics of the alloy.As the microstructure is controlled by forging process, numerical models are developed to predict relevant microstructural data such as grain characteristics which are related to the processing parameters. Based on experimental studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 4 publications
2
22
0
Order By: Relevance
“…In this version, the gas turbine disk is typically produced by 'hot-die' forging followed by aging. Grain refinement during forging is critical in this process for improved LCF life of the disk [3,4]. It is desirable that the fatigue critical disks are produced with a fine grained microstructure in the range of 5-20 μm to maximize fatigue benefits.…”
Section: Introductionmentioning
confidence: 99%
“…In this version, the gas turbine disk is typically produced by 'hot-die' forging followed by aging. Grain refinement during forging is critical in this process for improved LCF life of the disk [3,4]. It is desirable that the fatigue critical disks are produced with a fine grained microstructure in the range of 5-20 μm to maximize fatigue benefits.…”
Section: Introductionmentioning
confidence: 99%
“…In such homogeneous microstructures, the main crack very commonly initiates on a crystallographic cleavage on a grain located on the surface of the specimen [13]. The crack initiation mode is thus very similar to what has been identified on the AGG containing samples.…”
Section: µMmentioning
confidence: 56%
“…[1,3,[8][9][10]). The effect of grain size reduction ,assumed to be beneficial on fatigue lives, was more particularly studied for conventional and DA 718 alloys (see e.g.…”
Section: Fatigue Crack Initiation Sitesmentioning
confidence: 99%
“…The effect of grain size reduction ,assumed to be beneficial on fatigue lives, was more particularly studied for conventional and DA 718 alloys (see e.g. [1,2,10]). These studies confirmed that the reduction in grain size produces a significant increase in fatigue life, as shown in Figure 1, where the material is tested at 350°C and a frequency of 1Hz under strain controlled conditions (Rε t =ε min /ε max =0) [10,3].…”
Section: Fatigue Crack Initiation Sitesmentioning
confidence: 99%
See 1 more Smart Citation